113k views
0 votes
Please help me, I am writing everything down and following along diligently.

Please help me, I am writing everything down and following along diligently.-example-1

1 Answer

3 votes

Solution:

Given:


\begin{gathered} (d)/(dx)\lbrack g\lbrack f(2x)\rbrack\rbrack \\ at\text{ x = 1} \end{gathered}

At x = 1,


\begin{gathered} f(2x)=f(2(1))=f(2) \\ \\ \text{From the table given, } \\ f(2)=1 \end{gathered}
\begin{gathered} g\lbrack f(2x)\rbrack=g(1) \\ \text{From the table,} \\ g(1)=1 \end{gathered}
\begin{gathered} (d)/(dx)\lbrack g\lbrack f(2x)\rbrack\rbrack=(d)/(dx)g(1) \\ (d)/(dx)g(1)=g^1(1) \\ \\ \text{From the table, } \\ g^1(1)=4 \end{gathered}

Therefore,


(d)/(dx)\lbrack g\lbrack f(2x)\rbrack\rbrack\text{ at x = 1 is 4}

Hence, the answer is 4.

Hence, the answer is 4.

Please help me, I am writing everything down and following along diligently.-example-1
User Ziyuan
by
6.1k points